An extended overview of natural gas use embodied in world economy and supply chains: Policy implications from a time series analysis. (February 2020) - Kan, Siyi; Chen, Bin; Meng, Jing; Chen, Guoqian
Abstract: As an extension of our previous study on natural gas use in world economy (Kan et al., Energy Policy 124 (2019) 215–225), this paper explores policy implications based on a time series analysis uncovering the evolution of natural gas use embodied in global supply chains during 2000-2011. Due to increasing gas supply from gas-rich regions to gas-scarce regions and outsourcing of energy-intensive industries, trade imbalance of embodied natural gas is intensifying globally, corresponding to strengthening gas resource relocation and environmental stress shift. Regarding trade patterns, EU and Russia remain the leading (net) importer and exporter of embodied gas, respectively. And global trade relations are diversifying over time, with more suppliers and recipients joining the international trade. Based on the New Policies Scenario provided by IEA, a long term forecast of embodied gas use illustrates need to prepare for a world with changing energy mix, with respect to growing availability of low-cost natural gas and robust demand growth coming from emerging economies, especially China, who is struggling to fight against air pollution through coal-to-gas switch. Potential room to expand natural gas utilization is also targeted, and the expansion requires coordination of all the agents in global supply chains. Highlights: Evolution of natural gas use across global supply chains in 2000-2011 is studied. Embodied gas use is largest in EU and USA and grows fastest in China and Russia. Gas is increasingly embodied in trade, with EU/Russia as leading importer/exporter. Trade imbalance of embodied gas is intensifying, trade relations are diversifying. Embodied gas use is expected to grow, led by EU, USA and many emerging economies.